CUSTOMER RELATIONSHIP MANAGEMENT (CRM), KUALITAS PELAYANAN DAN PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS PEMASOK TANDAN BUAH SEGAR (TBS) PADA PT PERKEBUNAN NUSANTARA V-PEKANBARU - Hamdi, Amrizal; Indarti, Sri; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
The research seeks to analyze the effect of the Customer Relationship Management (CRM), Service Quality on Customer Satisfaction and Loyalty Supplier of Fresh Fruit Bunches and Customer Satisfaction on Loyalty Supplier of Fresh Fruit Bunches in PTPN V-Pekanbaru.The numbers of respondents involved were 127 respondents supplier of fresh fruit bunches in PTPN V used probability sampling with sample types using stratified random sampling. The data collection including interview, observation and questioner analyzed using Structural Equation Modeling (SEM) analysis.Based on statistics analysis results there were several conclusion as follows: The first customer relationship management is significant and positive effect on satisfaction supplier fresh fruit bunches (FFB), Second service quality is significant and positive effect on satisfaction supplier of fresh fruit bunches (FFB), third customer relationship management is not significant and positive effect on loyalty supplier of fresh fruit bunches (FFB), fourth the service quality is significant and positive effect on loyalty of suppliers of fresh fruit bunches (FFB), Fifth the satisfaction is not significant and positive effect on loyalty of suppliers of fresh fruit bunches (FFB), sixth generally loyalty and satisfaction of suppliers is already in the good category.Based on research result of the study, suggested the following matters: first the increase of customer relationship management is more focused on continuity marketing and one-to-one marketing. second the increase of quality of service more focused on reliability, empathy, and responsiveness, third enhancement supplier loyalty must be directed so that suppliers increasingly recommending to suppliers other fresh fruit bunches to supply fresh fruit bunches of oil mill PTPN V.